Analisa Ukuran Partikel Serbuk Komposit NiCrAl dengan Penambahan Reaktif Elemen untuk Aplikasi Lapisan Tahan Panas [Particle Size Analysis of NiCrAl Composite Powders with Reactive Elements Addition for Thermal Barrier Coating Applications] - Resetiana Dwi Desiati; Eni Sugiarti; Safitry Ramandhany (National Research and Innovation Agency (BRIN), 2018)
In this paper we discuss about the particle size of NiCrAl powder in addition to reactive elements, i.e. yttrium (Y), silicon (Si), hafnium (Hf), and zirconium (Zr) to produce compound powder of NiCrAlY, NiCrAlSi, NiCrAlYSi, NiCrAlHf, and NiCrAlZr produced by milling process using ball mill for 36 hours at rotating speed of 25 Hz or 1500 rpm and the ball to powder ratio (BPR) of 1:2. Scanning electron microscopy (SEM) was used to characterize the powder sample to understand the morphology of the sample such as particle shape and size. Digital picture of SEM results was analyzed using free software ImageJ to understand the particle size and the results was compared by using characterization results of Particle Size Analizer (PSA). Analysis of NiCrAl powder on at 0 hour (before milling) has a value of 44.04 μm based on PSA data, while based on ImageJ processing data NiCrAl powder has an average value of 46.98 μm. On the contrary, the PSA data on the classification of NiCrAl powder after 36 hours of milling time has a particle size of 71.12 μm whereas ImageJ processing data has an average value of 67.93 μm. These analysis methods have also been applied to NiCrAlSi, NiCrAlYSi, NiCrAlHf, and NiCrAlZr powders. Therefore, analysis results reveal that the digital processing of SEM image using ImageJ has an accuracy value of abaut 80% compared with PSA data. It is caused by the shape of powder sample which was not homogenous and not well-distributed. In addition, the SEM results show that the particle size of compound powder of NiCrAl, NiCrAlY, NiCrAlSi, NiCrAlYSi, NiCrAlHf, and NiCrAlZr after 36 hours was larger than the initial condition or 0 hours of milling time due to agglomeration and cold welding during milling process. The addition of reactive elements with small compositions to NiCrAl has no impact on particle size. AbstrakDalam makalah ini dibahas mengenai ukuran sampel serbuk NiCrAl yang ditambahkan reaktif elemen yitrium (Y), silikon (Si), hafnium (Hf), dan zirconium (Zr) menjadi paduan NiCrAlY, NiCrAlSi, NiCrAlYSi, NiCrAlHf, NiCrAlZr dengan proses milling menggunakan ball mill selama 36 jam dengan kecepatan milling 25 Hz atau 1500 rpm dan perbandingan antara serbuk dengan ball mill adalah 1:2. Scanning electron microscopy (SEM) digunakan untuk mengkarakterisasi sampel serbuk yang bertujuan untuk mengetahui morfologi sampel seperti bentuk dan ukuran partikel. Gambar digital dari hasil karakterisasi SEM diolah menggunakan software ImageJ untuk mengetahui ukuran partikelnya dan hasilnya pengukurannya dibandingkan dengan data hasil karakterisasi menggunakan Particle Size Analizer (PSA). Berdasarkan hasil analisa dapat diketahui bahwa pengolahan gambar dijital SEM menggunakan ImageJ memiliki keakuratan kurang lebih sebesar 80%. Hal ini disebabkan dari bentuk sampel powder yang tidak homogen dan sebarannya yang tidak merata. Selain itu pula dapat diketahui juga bahwa sampel serbuk paduan NiCrAl, NiCrAlY, NiCrAlSi, NiCrAlYSi, NiCrAlHf, NiCrAlZr setelah pemilingan selama 36 jam mengalami perbesaran ukuran dari kondisi awal atau 0 jam yang disebabkan selama proses pemilingan mengalami aglomerasi dan coldwelding.